2019
DOI: 10.17843/rpmesp.2019.363.4366
|View full text |Cite
|
Sign up to set email alerts
|

Resistencia antimicrobiana de cepas comensales de Escherichia coli en niños de dos comunidades rurales peruanas

Abstract: Médico cirujano, b bióloga. El presente estudio forma parte de la tesis: Alzamora-Schmatz MC, Ferraro-Vidal VM, Echevarría-Rosas Morán AC. Resistencia a los antibióticos de cepas comensales de E. coli aisladas en heces de niños sanos de comunidades rurales del Perú.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Resistance to ampicillin, cotrimoxazole, tetracycline, chloramphenicol, nalidixic acid and ciprofloxacin was reported in E. coli recovered among children in a periurban population in Peru [ 14 ]. Likewise, there is evidence of AMR in enterobacteria found in children across different environments: rural towns of the Amazon and Andean regions, periurban slums in desert coastal cities, and villages in the Amazon region [ 15 , 16 , 17 ]. Nevertheless, most of the evidence for AMR in human populations is focused on urban and periurban settings rather than rural areas [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to ampicillin, cotrimoxazole, tetracycline, chloramphenicol, nalidixic acid and ciprofloxacin was reported in E. coli recovered among children in a periurban population in Peru [ 14 ]. Likewise, there is evidence of AMR in enterobacteria found in children across different environments: rural towns of the Amazon and Andean regions, periurban slums in desert coastal cities, and villages in the Amazon region [ 15 , 16 , 17 ]. Nevertheless, most of the evidence for AMR in human populations is focused on urban and periurban settings rather than rural areas [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, there is evidence of AMR in enterobacteria found in children across different environments: rural towns of the Amazon and Andean regions, periurban slums in desert coastal cities, and villages in the Amazon region [ 15 , 16 , 17 ]. Nevertheless, most of the evidence for AMR in human populations is focused on urban and periurban settings rather than rural areas [ 15 ]. On the other hand, extended-spectrum β-lactamases (ESBL) production is common in E. coli and other enterobacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies reported the AMR levels of human commensal E. coli. Of these, 1 analyzed samples from Lima [49], another samples from San Martin and Cusco [53], and the remaining study analyzed samples from 4 Peruvian departments, including Lima [52].…”
Section: Human Commensal Escherichia Colimentioning
confidence: 99%
“…This scenario showing that the number of studies reporting the levels of AMR among human commensal E. coli in Peru are scarce and mostly outdated, with all but one referring E. coli collected before 2009, with this panorama also extended to the 3 non-included studies [28,49,50,51,52]. The remaining study analyzing isolates collected on 2014-2015 [53]. This scenario is probably common to a series of low-and middle-income countries for which this type of data is scarce or often unavailable.…”
Section: Human Commensal Escherichia Colimentioning
confidence: 99%
“…Specifically, in Latin America (LA), human and veterinary use of antibiotics is loosely regulated, and antibiotics are readily available over the counter without prescription [ 20 , 21 , 22 ]. In addition to urban clinical settings [ 23 , 24 , 25 ], rural environments have been linked to AMR in Latin America [ 17 , 26 , 27 ]. In such settings, small-scale animal farming is predominant [ 28 , 29 ] and animal excreta are a key driver of faecal contamination in domestic human environs [ 30 ].…”
Section: Introductionmentioning
confidence: 99%